Episodic Long‐Term Exhumation of the Tianshan Orogenic Belt: New Insights From Multiple Low‐Temperature Thermochronometers. Issue 4 (25th April 2023) - Yin, Jiyuan; Wang, Yannan; Hodges, K. V.; Xiao, Wenjiao; Thomson, Stuart N.; Chen, Wen; Yuan, Chao; Sun, Min; Cai, Keda; Sun, Jingbo
Abstract: The Tianshan orogenic belt, part of the Central Asian Orogenic Belt, offers an opportunity to examine the complexities of an orogenic system that records long‐term intracontinental deformation. The Tianshan have been reactivated multiple times since the Mesozoic, but the mechanisms and driving forces of these various orogenic events are not well constrained. Moreover, the spatial exhumation pattern of the entire Tianshan remains poorly studied. We present new zircon and apatite (U‐Th)/He and apatite fission track thermochronological data for samples from the northwestern part of the Chinese Western Tianshan. They indicate three distinctive phases of rapid cooling in the late Carboniferous‐early Permian, Late Triassic‐Early Jurassic, and Cretaceous. The first phase can be linked to uplift and exhumation related to the subduction/closure of the Paleo‐Asian Ocean, while the episodic cooling during the Late Triassic‐Early Jurassic (250–190 Ma) and Cretaceous (115–80 Ma) are interpreted as related to uplift and exhumation associated with strike‐slip deformation and Mesozoic clockwise or anticlockwise rotation of the Junggar basin. Our new data, in concert with a compilation of previously published data from elsewhere in the region, reveal that the Tianshan underwent a greater amount of exhumation in the southern section, and less exhumation took place to the north. All available data also support the notion that the exhumation process has been essentially the same in tectonic blocks along strike since late Paleozoic. During the Cenozoic, the Tianshan experienced large‐scale, rapid exhumation starting in the late Miocene (12–10 Ma) and not the early Miocene as has been previously proposed. Key Points: Pulsed exhumation episodes in the Tianshan orogenic belt are interpreted as the result of differential rotation of local crustal blocks The late Paleozoic to Cenozoic regional exhumation was greatest in southwest Tianshan and lessened progressively to the north and east New data and regional compilation show that the late Oligocene deformation event was local and did not result in regional exhumation